Reflections on Human Rights and Democracy in Indonesia: The Struggle of Victims Seeking Justice in the Kamisan Action, Amidst the 2024 Presidential Election Vacuum. - Nazwa St May; Dedi Mulyadi; Siti Maesaroh; Fajar Muhammad Kartiwa (PT Syamilah Literasi Islami, 2024)
During Indonesia's reformation era, past human rights violations weren't addressed through ad hoc trials despite changing leadership. Ahead of the 2024 President Election, amidst heightened political competition, the issue seemed neglected. Foreign media focused on this, particularly due to Gibran, President Jokowi's son, discussing political dynasties, and controversies surrounding a candidate accused of human rights violations, banned from entering the US. 1) The author aims to analyze the government's policy on the Kamisan Action, supporting human rights trials in Indonesia, and evaluate president candidate' commitment to addressing human rights violations. It's hoped the 2024 elected President prioritizes resolving human rights issues and increases public awareness of ongoing violations. 2) The research adopts a normative juridical approach. 3) Findings: Efforts to address past human rights violations since BJ Habibie's time haven't fully resolved the issue. The planned Ad Hoc Court under Law No. 26 of 2000 remains unimplemented, indicating a lack of state commitment to protecting human rights. The Kamisan Action continues its fight for justice, but hopes were dashed with leadership changes. In the 2024 president election, only candidate pair Anies Rasyid Baswedan-Muhaimin Iskandar, and candidate pair Ganjar Pranowo-Mahfud MD prioritize human rights. Prabowo's victory, despite allegations of involvement in human rights violations, left the Kamisan Action disillusioned. 4) Conclusion, however there's a possibility of establishing an ad hoc court under the current administration. Ensuring perpetrators face justice is crucial to prevent ongoing injustice and implicate the state in human rights violations by not resolving the issue.